A virtual reality system for motor and cognitive neurorehabilitation - Cameirão, Mónica S. (2022)
Here we present a virtual reality system developed for the rehabilitation of motor deficits following stroke. A virtual reality augmented feedback system or the Rehabilitation Gaming System (RGS), presents the patient with a training scenario that is designed to promote the rehabilitation of the upper extremities. RGS allows rapid and online diagnostics of the patient’s capabilities and the dynamic personalization of the rehabilitation scenario. We present the basic design considerations between RGS, its neuroscientific roots and preliminary results obtained with stroke patients that illustrate the main properties of the system.